Analysis of Vina Muliana's Online Identity on the Tik Tok account @Vmuliana in Maintaining the Authenticity of the Identity Constructed: Analisis Identitas Online Vina Muliana pada akun Tik Tok @Vmuliana dalam Mempertahankan Keaslian Identitas yang Dikonstruksi. - Nikmah, Hadiyatun; Febriana, Poppy (Procedia of Social Sciences and Humanities, 2025)
In today's digital era, it is important to be able to build an online identity on social media. Online identity is the extension of one's physical existence into the virtual domain. Online identity has become an important aspect of our lives. Moreover, this includes influence in the digital space or can be called social media, privacy challenges, identity theory and about the dynamics in cyberspace. One of the most popular social media is Tik Tok. This research aims to find out how Vina Muliana shaping online identity, managing context collapse, as well as threats, challenges and opportunities for privacy and surveillance on Tik Tok social media. This type of research is qualitative. The research results show that Vina Muliana succeeded in building her online identity with an interesting strategy. Apart from that, the results show that Vina Muliana is able to overcome context collapse and also overcome threats to privacy and surveillance on Tik Tok social media. Highlights: Strategic Online Identity Building – Vina Muliana successfully shapes her online identity on TikTok through engaging content and a well-planned digital persona. Managing Context Collapse – She effectively navigates different audience expectations, maintaining consistency while adapting to various online interactions. Privacy & Surveillance Challenges – Vina Muliana proactively addresses privacy risks and surveillance concerns, balancing visibility with security on TikTok. Keywords: Social Media, Online Identity, Tik Tok